2007
DOI: 10.1002/jor.20335
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant neuropeptides can improve neuropathic ligament healing in a rat model

Abstract: Diminished healing in neuropathic tissues suggests an important regulatory role for peripheral neurogenic factors in connective tissue healing. Although neurogenic factors, including neuropeptides, can induce cell proliferation and influence inflammatory cell chemotaxis in vitro, there is little appreciation of the potential of neuropeptides to affect connective tissue healing in vivo. We created both efferent and afferent peripheral neuropathies in 55 female Wistar rats. First, we showed that neuropathy led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 30 publications
(30 reference statements)
3
16
0
Order By: Relevance
“…Today there are no available treatments which dramatically can promote tendon healing, especially in tendinopathic patients. The present study corroborates the conception that exogenous sensory neuropeptide SP supply can enhance tendon/ligament healing (Burssens et al, 2005; Steyaert et al, 2006; Grorud et al, 2007). Biomechanical studies suggest that SP may today be one of the most potent mediators to affect soft tissue healing (Grorud et al, 2007).…”
Section: Perspectivessupporting
confidence: 90%
“…Today there are no available treatments which dramatically can promote tendon healing, especially in tendinopathic patients. The present study corroborates the conception that exogenous sensory neuropeptide SP supply can enhance tendon/ligament healing (Burssens et al, 2005; Steyaert et al, 2006; Grorud et al, 2007). Biomechanical studies suggest that SP may today be one of the most potent mediators to affect soft tissue healing (Grorud et al, 2007).…”
Section: Perspectivessupporting
confidence: 90%
“…To see this illustration in color, the reader is referred to the web version of this article at www .liebertpub.com/wound of intact, uninjured MCLs. 41 The supply of SP, VIP, and NPY also significantly improved the histological appearance of the healing MCLs. Treated ligaments showed more organized scars and the appearance of increased matrix production.…”
mentioning
confidence: 91%
“…37 One study assessed the effect of exogenous neuropeptide administration on the healing of denervated ligaments in rats. 41 The aim was to restore the neuronal supply to improve the healing responses of the medial collateral ligament (MCL) in joints partially denervated by femoral nerve transection or surgical sympathectomy. In this study, exogenous SP, VIP, and NPY all led to improved healing of denervated MCLs.…”
mentioning
confidence: 99%
“…Therefore, our results showed that, comparing with the normal knees, there was a signiWcant decrease in total innervation of the PCL including a subpopulation of proprioceptive and sympathetic nerves in the OA knees. Because peripheral nerves within the ligament play an essential role in homeostasis of ligaments and joints [19,20], the decrease in total innervations can be detrimental to the structural integrity of ligaments and joints.…”
Section: Discussionmentioning
confidence: 99%